Resin composition and molded article thereof

The resin composition, featuring a polycarbonate resin with a spiro ring structure, an acrylic resin, an impact modifier, and a specific ion-pair compound, effectively addresses the challenges of achieving thermal stability, surface hardness, impact resistance, and sustained antistatic properties in polycarbonate resin applications.

JP7658760B2Active Publication Date: 2025-04-08TEIJIN LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2021037503
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-09
Publication Date
2025-04-08
Estimated Expiration
2041-03-09

AI Technical Summary

Technical Problem

Current resin compositions used in polycarbonate resin applications lack simultaneous achievement of excellent thermal stability, surface hardness, impact resistance, and sustained antistatic properties without compromising surface hardness.

Method used

A resin composition comprising a polycarbonate resin with a specific spiro ring structure, an acrylic resin, an impact modifier, and an ion-pair compound with a melting point of 100°C or less and a 10% weight reduction temperature of 250°C or higher, which satisfies specific contact angle formulas and includes a cation of organic ammonium or phosphonium ions or an anion of sulfonylimide or fluorosulfonate ions.

Benefits of technology

The composition achieves enhanced thermal stability, surface hardness, impact resistance, and sustained antistatic properties, addressing the limitations of existing resin compositions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007658760000001
    Figure 0007658760000001
  • Figure 0007658760000002
    Figure 0007658760000002
  • Figure 0007658760000003
    Figure 0007658760000003
Patent Text Reader

Abstract

To provide a resin composition having a sustainable antistatic property without deteriorating surface hardness compared with a resin to be a base material, while having excellent thermal stability and surface hardness, and impact resistance, and to provide its molding.SOLUTION: A resin composition containing 5 to 60 pts.mass of an impact resistance modifier (C), and 0.1 to 10 pts.mass of an ion pair compound (D) based on a total of 100 pts.mass of a polycarbonate resin (A) and an acrylic resin (B) containing 5 to 85 mol% of a carbonate structural unit (a) represented by a following formula (1) out of 100 mol% of all carbonate structural units, in which the ion pair compound has a melting point of 100°C or less, a 10% weight loss temperature of 250°C or higher as measured by TG-TDA and, satisfies a following formula [I]. RI>RD-30 [I] (RI is a contact angle (°) of a water droplet of a resin composition containing 2 pts.mass of a content of an ion-pair compound, and RD is the contact angle (°) of a water droplet of a polycarbonate resin.)SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition containing a specific polycarbonate resin, an acrylic resin, an impact modifier and a specific antistatic agent. [Background technology]

[0002] Conventionally, methacrylic resins, polycarbonate resins (hereinafter sometimes referred to as PC), etc. are known as transparent resins, and these resins are used in a wide range of fields such as electrical and electronic components, optical components, automotive components, and mechanical components in the form of molded products, films, sheets, etc.

[0003] Methacrylic acid resins such as polymethyl methacrylate (hereinafter sometimes referred to as PMMA) have high transparency and high surface hardness (pencil hardness H to 3H), and are widely used as optical materials such as lenses and optical fibers. However, their glass transition temperature is low at about 100°C, and their heat resistance is poor, limiting their use in fields requiring heat resistance. Another problem is that they have low impact resistance.

[0004] Polycarbonate resins made from bisphenol A are widely used in vehicles and building materials because of their excellent heat resistance, impact resistance, flame retardancy, and transparency. Among these applications, high weather resistance is required, especially for outdoor use, but the weather resistance of polycarbonate resins is generally not as good as that of other transparent materials such as acrylic resins, and yellowing and devitrification occur when exposed to the outdoors. In addition, there is a problem that the surface is very soft (pencil hardness 4B to 2B) and easily scratched.

[0005] It is known that blends of PC and PMMA are essentially incompatible and produce opaque materials. For example, Patent Document 1 shows that blends of PC and PMMA are opaque and do not exhibit the physical properties of both polymers.

[0006] A resin composition using a polycarbonate resin having a special structure and an acrylic resin has been reported (Patent Document 2), which has achieved excellent transparency, weather resistance, and surface hardness. However, according to the study by the present inventors, the resin composition described in Patent Document 2 has a problem with impact resistance.

[0007] These polycarbonate resins and acrylic resins have poor antistatic properties, and there is a problem that dust easily adheres to the surface of the molded product due to static electricity. Therefore, in order to solve these problems, a method of blending hydrophilic polyamide-based polymers such as polyetheresteramide and polyetheramide to impart antistatic performance is known (Patent Document 3). However, although hydrophilic polyamide-based polymers have the advantage of being able to impart sustained antistatic properties, there is a problem that they reduce surface hardness and deflection temperature under load. As another method for solving the problem of antistatic properties, a method of adding a surfactant, for example, a method of using a sulfonic acid phosphonium salt (Patent Document 4) and a method of using a surfactant such as a glycerin fatty acid ester (Patent Document 5) have been proposed. In addition, a method of using a specific ion pair compound (Patent Document 6) has also been proposed. However, the methods described in Patent Documents 4 to 6 have not been reported on sustained antistatic properties or their effects on surface hardness, and verification is insufficient. In addition, some surfactants and ion-pair compounds have a low thermal decomposition temperature, which means that not only do the antistatic agents decompose during processing, but also the decomposition products of the antistatic agents cause the polycarbonate resin to decompose. Furthermore, verification of their thermal stability (hereinafter referred to as thermal stability) has been insufficient.

[0008] Therefore, in the polycarbonate resin composition, good thermal stability, surface hardness, and impact resistance are obtained. Thus, no composition has been reported so far that has sustained antistatic properties while having a surface hardness that does not decrease compared to that of the base resin. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] U.S. Pat. No. 4,319,003 [Patent Document 2] JP 2015-232091 A [Patent Document 3] JP 2002-129026 A [Patent Document 4] Patent No. 4606762 [Patent Document 5] Patent No. 6215717 [Patent Document 6] Patent No. 6724737 Summary of the Invention [Problem to be solved by the invention]

[0010] An object of the present invention is to provide a resin composition having good thermal stability, surface hardness and impact resistance, without a decrease in surface hardness compared to the base resin, and having sustained antistatic properties, and to provide a molded article thereof. [Means for solving the problem]

[0011] Means for Solving the Problems The present inventors have conducted extensive research and have discovered that by adding an acrylic resin, an impact modifier, and an ion pair compound having a specific structure to a polycarbonate resin containing a specific spiro ring structure, a resin composition having excellent properties such as thermal stability, surface hardness, impact resistance, and sustained antistatic properties can be obtained, thereby completing the present invention.

[0012] That is, according to the present invention, the object of the invention is achieved as follows.

[0013] 1. A resin composition comprising 100 parts by weight in total of a polycarbonate resin (A) containing 5 to 85 mol % of carbonate structural units (a) represented by the following formula (1) out of 100 mol % of all carbonate structural units, and an acrylic resin (B), 5 to 60 parts by weight of an impact modifier (C) and 0.1 to 10 parts by weight of an ion pair compound (D), wherein the ion pair compound has a melting point of 100°C or lower, a 10% weight loss temperature measured by TG-TDA of 250°C or higher, and satisfies the following formula [I]. R I >R D -30[I] (In the formula, R I is the contact angle (°) of a water droplet of a resin composition having an ion pair compound content of 2 parts by weight per 100 parts by weight of polycarbonate resin, and R D is the contact angle of a water droplet on polycarbonate resin (°).

[0014] [ka]

[0015] (In the formula, W represents an alkylene group having 1 to 20 carbon atoms or a cycloalkylene group having 6 to 20 carbon atoms, R represents a branched or linear alkyl group having 1 to 20 carbon atoms or a cycloalkyl group having 6 to 20 carbon atoms which may have a substituent, and m represents an integer of 0 to 10.)

[0016] 2. The polycarbonate resin (A) contains a carbonate structural unit represented by the formula (1) ( 2. The resin composition according to item 1 above, which comprises (a) and another carbonate structural unit (b), the carbonate structural unit (b) being a carbonate structural unit (b) derived from at least one compound selected from the group consisting of an aliphatic diol compound, an alicyclic diol compound, and an aromatic dihydroxy compound.

[0017] 3. The resin composition according to item 1 or 2 above, wherein the weight ratio of the polycarbonate resin (A) to the acrylic resin (B) is 30:70 to 99:1.

[0018] 4. The resin composition according to any one of items 1 to 3 above, wherein the acrylic resin (B) contains 40 to 100 mol % of structural units derived from methyl methacrylate.

[0019] 5. The resin composition according to any one of items 1 to 4 above, wherein the ion pair compound has a 10% weight loss temperature measured by TG-TDA of 270°C or higher and satisfies the following formula [II]: R I >R D -20[II] (In the formula, R1 is the contact angle (°) of a water droplet of a resin composition having an ion pair compound content of 2 parts by weight per 100 parts by weight of polycarbonate resin, and R D is the contact angle of a water droplet on polycarbonate resin (°).

[0020] 6. The resin composition according to any one of items 1 to 5 above, wherein the cation of the ion-pair compound contains an organic ammonium ion or an organic phosphonium ion represented by the following formula (3), or the anion of the ion-pair compound contains a sulfonylimide ion represented by the following formula (4) or a fluorosulfonate ion represented by the following formula (5).

[0021] [ka] [In the formula, R1 and R2 represent a hydrocarbon group, and M represents a N atom or a P atom.]

[0022] [ka] [In the formula, R3 and R4 each represent a perfluoroalkyl group.]

[0023] [ka] [In the formula, R5 represents a perfluoroalkyl group.]

[0024] 7. The resin composition according to any one of items 1 to 6 above, wherein the cation of the ion-pair compound contains an organic phosphonium ion represented by the following formula (6), or the anion of the ion-pair compound contains a sulfonylimide ion represented by the following formula (7) or a fluorosulfonate ion represented by the following formula (8).

[0025] [ka] [In the formula, R1 represents an alkyl group having 1 or more carbon atoms, and R2 represents an alkyl group having 4 or more carbon atoms.]

[0026] [ka] [In the formula, R3 and R4 each represent a perfluoroalkyl group having 1 to 4 carbon atoms.]

[0027] [ka] [In the formula, R5 represents a perfluoroalkyl group having 1 to 4 carbon atoms.]

[0028] 8. The resin composition according to any one of items 1 to 7 above, wherein the cation of the ion-pair compound contains an organic phosphonium ion represented by the following formula (9), or the anion of the ion-pair compound contains a sulfonylimide ion represented by the following formula (10) or a fluorosulfonate ion represented by the following formula (11).

[0029] [ka] [In the formula, R1 represents an alkyl group having 4 or more carbon atoms, and R2 represents an alkyl group having 12 or more carbon atoms.]

[0030] [ka] [In the formula, R3 and R4 each represent a trifluoromethyl group.]

[0031] [ka] [In the formula, R5 represents a perfluorobutyl group.]

[0032] 9. Charpy notched impact strength measured according to ISO 179 is 10 kJ / m 2 9. The resin composition according to any one of items 1 to 8 above.

[0033] 10. The resin composition according to any one of items 1 to 9 above, which has a pencil hardness of H or more as measured according to JIS K5400.

[0034] 11. The surface resistivity of a molded product is 1 x 10 15 11. The resin composition according to any one of items 1 to 10, wherein the viscosity is (Ω / □) or less.

[0035] 12. A molded article obtained by injection molding the resin composition according to any one of items 1 to 11 above.

[0036] 13. A film or sheet formed from the resin composition according to any one of items 1 to 11 above. Effect of the Invention

[0037] According to the present invention, by adding an impact modifier and an ion pair compound having a specific structure to a resin component of a polycarbonate resin containing a specific spiro ring structure and an acrylic resin, it is possible to provide a resin composition having excellent properties such as thermal stability, surface hardness, impact resistance, and sustained antistatic properties, and therefore the industrial effects achieved are exceptional. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0038] The present invention will be described in detail below.

[0039] (Polycarbonate resin (A)) The polycarbonate resin used in the resin composition of the present invention is a polycarbonate resin containing 5 to 85 mol % of carbonate structural units (a) represented by the following formula (1) in 100 mol % of all carbonate structural units.

[0040] [ka]

[0041] (In the formula, W represents an alkylene group having 1 to 20 carbon atoms or a cycloalkylene group having 6 to 20 carbon atoms, R represents a branched or linear alkyl group having 1 to 20 carbon atoms or a cycloalkyl group having 6 to 20 carbon atoms which may have a substituent, and m represents an integer of 0 to 10.)

[0042] The carbonate structural unit (a) represented by the above formula (1) is derived from a diol having a spiro ring structure. Examples of the diol compound having such a spiro ring structure include alicyclic diol compounds such as 3,9-bis(2-hydroxyethyl)-2,4,8,10-tetraoxaspiro(5.5)undecane, 3,9-bis(2-hydroxy-1,1-dimethylethyl)-2,4,8,10-tetraoxaspiro(5.5)undecane, 3,9-bis(2-hydroxy-1,1-diethylethyl)-2,4,8,10-tetraoxaspiro(5.5)undecane, and 3,9-bis(2-hydroxy-1,1-dipropylethyl)-2,4,8,10-tetraoxaspiro(5.5)undecane.

[0043] Preferably, 3,9-bis(2-hydroxy-1,1-dimethylethyl)-2,4,8,10-tetraoxaspiro(5.5)undecane is used.

[0044] The polycarbonate resin used in the resin composition of the present invention contains 5 to 85 mol %, preferably 10 to 80 mol %, more preferably 15 to 75 mol %, and even more preferably 20 to 70 mol % of the carbonate structural unit (a) represented by the above formula (1) in 100 mol % of all carbonate structural units. When the carbonate structural unit (a) is within the above range, the resin composition does not become cloudy due to phase separation during extrusion or molding of the resin composition with the acrylic resin, and polymerization is easy without crystallization during polymerization of the polycarbonate resin, which is preferable.

[0045] The polycarbonate resin used in the resin composition of the present invention contains the carbonate structural unit (a) represented by the above formula (1), and is used as a copolymer with another carbonate structural unit (b).

[0046] The carbonate structural unit (b) is preferably a carbonate structural unit (b) derived from at least one compound selected from the group consisting of an aliphatic diol compound, an alicyclic diol compound, and an aromatic dihydroxy compound. From the standpoint of surface hardness and weather resistance, the carbonate structural unit (b) is preferably a carbonate structural unit (b) derived from at least one compound selected from the group consisting of an aliphatic diol compound and an alicyclic diol compound.

[0047] Aliphatic diol compounds include 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,12-dodecanediol, 2-methyl-1,3-propanediol, neopentyl glycol, 3-methyl-1,5-pentanediol, 2-n-butyl-2-ethyl-1,3-propanediol, and 2,2-diethyl-1,3-propanediol. Examples of the diol include 2,4-diethyl-1,5-pentanediol, 1,2-hexane glycol, 1,2-octyl glycol, 2-ethyl-1,3-hexanediol, 2,3-diisobutyl-1,3-propanediol, 2,2-diisoamyl-1,3-propanediol, and 2-methyl-2-propyl-1,3-propanediol. Of these, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, and 1,12-dodecanediol are preferably used.

[0048] Examples of the alicyclic diol compound include cyclohexanediols such as 1,2-cyclohexanediol, 1,3-cyclohexanediol, 1,4-cyclohexanediol, and 2-methyl-1,4-cyclohexanediol; cyclohexanedimethanols such as 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, and 1,4-cyclohexanedimethanol; norbornane dimethanols such as 2,3-norbornane dimethanol and 2,5-norbornane dimethanol; tricyclodecane dimethanol, pentacyclopentadecane dimethanol, 1,3-adamantanediol, 2,2-adamantanediol, decalin dimethanol, 2,2,4,4-tetramethyl-1,3-cyclobutanediol, and isosorbide; and preferably used are cyclohexanedimethanol and isosorbide.

[0049] Examples of aromatic dihydroxy compounds include α,α'-bis(4-hydroxyphenyl)-m-diisopropylbenzene (bisphenol M), 9,9-bis(4-hydroxy-3-methylphenyl)fluorene, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 4,4'-dihydroxy-3,3'-dimethyldiphenyl sulfide, bisphenol A, 2,2-bis(4-hydroxy-3-methylphenyl)propane (bisphenol C), 2,2-bis(4-hydroxyphenyl)-1,1,1,3,3,3-hexafluoropropane (bisphenol AF), and 1,1-bis(4-hydroxyphenyl)decane, with bisphenol A being preferred.

[0050] The carbonate structural unit (b) is preferably contained in an amount of 15 to 95 mol %, more preferably 20 to 90 mol %, further preferably 25 to 85 mol %, and particularly preferably 30 to 80 mol %, based on 100 mol % of all carbonate structural units. When the carbonate structural unit (b) is within the above range, a resin composition having an excellent balance of thermal stability, surface hardness, impact resistance, and sustained antistatic properties can be obtained.

[0051] (Production method of polycarbonate resin (A)) The polycarbonate resin used in the resin composition of the present invention is produced by a reaction means known per se for producing ordinary polycarbonate resins, for example, a method of reacting a diol component with a carbonate precursor such as a carbonic acid diester. The basic means for these production methods will now be briefly described.

[0052] The transesterification reaction using a carbonic acid diester as a carbonate precursor is carried out by stirring a predetermined ratio of a diol component and a carbonic acid diester under heating in an inert gas atmosphere, and distilling off the resulting alcohol or phenol. The temperature varies depending on the boiling point of coal or phenols, but is usually in the range of 120 to 300°C. The reaction is completed by reducing the pressure from the beginning and distilling off the alcohol or phenols produced. If necessary, a terminal terminator, an antioxidant, etc. may be added.

[0053] The carbonic acid diester used in the transesterification reaction includes esters of aryl groups and aralkyl groups having 6 to 12 carbon atoms, which may be substituted. Specific examples include diphenyl carbonate, ditolyl carbonate, bis(chlorophenyl) carbonate, and m-cresyl carbonate. Among these, diphenyl carbonate is particularly preferred. The amount of diphenyl carbonate used is preferably 0.97 to 1.10 mol, more preferably 1.00 to 1.06 mol, per mol of the total of the dihydroxy compounds.

[0054] In the melt polymerization method, a polymerization catalyst can be used to increase the polymerization rate. Examples of such a polymerization catalyst include alkali metal compounds, alkaline earth metal compounds, nitrogen-containing compounds, and metal compounds.

[0055] As such compounds, organic acid salts, inorganic salts, oxides, hydroxides, hydrides, alkoxides, quaternary ammonium hydroxides, etc. of alkali metals or alkaline earth metals are preferably used, and these compounds can be used alone or in combination.

[0056] Examples of alkali metal compounds include sodium hydroxide, potassium hydroxide, cesium hydroxide, lithium hydroxide, sodium hydrogen carbonate, sodium carbonate, potassium carbonate, cesium carbonate, lithium carbonate, sodium acetate, potassium acetate, cesium acetate, lithium acetate, sodium stearate, potassium stearate, cesium stearate, lithium stearate, sodium borohydride, sodium benzoate, potassium benzoate, cesium benzoate, lithium benzoate, disodium hydrogen phosphate, dipotassium hydrogen phosphate, dilithium hydrogen phosphate, disodium phenylphosphate, disodium salt, dipotassium salt, dicesium salt, and dilithium salt of bisphenol A, and sodium, potassium, cesium, and lithium salts of phenol.

[0057] Examples of alkaline earth metal compounds include magnesium hydroxide, calcium hydroxide, strontium hydroxide, barium hydroxide, magnesium carbonate, calcium carbonate, strontium carbonate, barium carbonate, magnesium diacetate, calcium diacetate, strontium diacetate, barium diacetate, and barium stearate.

[0058] Examples of the nitrogen-containing compound include quaternary ammonium hydroxides having an alkyl or aryl group, such as tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, and trimethylbenzylammonium hydroxide. Other examples include tertiary amines, such as triethylamine, dimethylbenzylamine, and triphenylamine, and imidazoles, such as 2-methylimidazole, 2-phenylimidazole, and benzimidazole. Other examples include bases or basic salts, such as ammonia, tetramethylammonium borohydride, tetrabutylammonium borohydride, tetrabutylammonium tetraphenylborate, and tetraphenylammonium tetraphenylborate.

[0059] Examples of the metal compound include zinc aluminum compounds, germanium compounds, organotin compounds, antimony compounds, manganese compounds, titanium compounds, zirconium compounds, etc. These compounds may be used alone or in combination of two or more.

[0060] The amount of the polymerization catalyst used is preferably 1×10 -9 ~1×10 -2 equivalent, preferably 1 x 10 -8 ~1×10 -5 equivalent, more preferably 1×10 -7 ~1×10 -3 is selected within the equivalent range.

[0061] A catalyst deactivator can also be added in the later stage of the reaction. Known catalyst deactivators can be effectively used as the catalyst deactivator, and among these, ammonium salts and phosphonium salts of sulfonic acid are preferred. Furthermore, salts of dodecylbenzenesulfonic acid such as tetrabutylphosphonium dodecylbenzenesulfonate and salts of paratoluenesulfonic acid such as tetrabutylammonium paratoluenesulfonate are preferred.

[0062] As the ester of sulfonic acid, methyl benzenesulfonate, ethyl benzenesulfonate, butyl benzenesulfonate, octyl benzenesulfonate, phenyl benzenesulfonate, methyl paratoluenesulfonate, ethyl paratoluenesulfonate, butyl paratoluenesulfonate, octyl paratoluenesulfonate, phenyl paratoluenesulfonate, etc. are preferably used. Among them, tetrabutylphosphonium dodecylbenzenesulfonate is most preferably used.

[0063] When at least one polymerization catalyst selected from alkali metal compounds and / or alkaline earth metal compounds is used, the amount of these catalyst deactivators used is preferably 0.5 to 50 mol, more preferably 0.5 to 10 mol, and even more preferably 0.8 to 5 mol, per mol of the catalyst.

[0064] (Specific viscosity of polycarbonate resin (A): η SP ) The specific viscosity (η SP ) is preferably 0.2 to 1.5. When the specific viscosity is in the range of 0.2 to 1.5, the strength and molding processability of the molded article become better. It is more preferably 0.25 to 1.0, further preferably 0.3 to 0.7, and particularly preferably 0.3 to 0.5.

[0065] The specific viscosity referred to in the present invention is determined by using an Ostwald viscometer to measure a solution in which 0.7 g of polycarbonate resin is dissolved in 100 ml of methylene chloride at 20°C. Specific viscosity (η SP )=(t-t0) / t0 [t0 is the number of seconds that methylene chloride falls, and t is the number of seconds that the sample solution falls]

[0066] The specific viscosity can be measured, for example, as follows. First, polycarbonate resin is dissolved in methylene chloride of 20 to 30 times its weight, and the soluble portion is collected by celite filtration. The solution is then removed and the mixture is thoroughly dried to obtain a solid soluble in methylene chloride. 0.7 g of the solid is dissolved in 100 ml of methylene chloride, and the specific viscosity at 20°C is determined using an Ostwald viscometer.

[0067] (Acrylic resin (B)) The acrylic resin used in the resin composition of the present invention is an acrylic resin as a thermoplastic resin. The following compounds can be mentioned as monomers used in the acrylic resin. For example, methyl methacrylate, methacrylic acid, methyl acrylate, acrylic acid, benzyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl (meth)acrylate, t-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, stearyl (meth)acrylate, glycidyl (meth)acrylate, hydroxypropyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, norbornyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, Examples of the acrylate include acrylate, acrylic (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-(meth)acryloyloxyethyl succinate, 2-(meth)acryloyloxyethyl maleate, 2-(meth)acryloyloxyethyl phthalate, 2-(meth)acryloyloxyethyl hexahydrophthalate, pentamethylpiperidyl (meth)acrylate, tetramethylpiperidyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, cyclopentyl methacrylate, cyclopentyl acrylate, cyclohexyl methacrylate, cyclohexyl acrylate, cycloheptyl methacrylate, cycloheptyl acrylate, cyclooctyl methacrylate, cyclooctyl acrylate, cyclododecyl methacrylate, and cyclododecyl acrylate.

[0068] These may be used by polymerizing one of them, or by polymerizing two or more of them. Among them, it is preferable to contain methyl methacrylate and / or methyl acrylate. In particular, it is preferable to contain 40 to 100 mol % of methyl methacrylate as a monomer component, more preferably 50 to 100 mol %, and even more preferably 60 to 99 mol %. When the ratio of methyl methacrylate as a monomer component is within the above range, the thermal decomposition resistance is excellent, molding defects such as silver are unlikely to occur during molding, and the heat distortion temperature is better. In addition, other monomers that can be polymerized with these acrylic monomers, such as polyolefin monomers and vinyl monomers, may be used in combination.

[0069] The molecular weight of the acrylic resin is not particularly limited, but as long as the weight-average molecular weight is within the range of 30,000 or more and 300,000 or less, a composition having excellent mechanical properties and heat resistance can be provided without causing poor appearance such as flow unevenness when molded into a composition.

[0070] The acrylic resin used in the resin composition of the present invention preferably has a specific viscosity in the range of 0.12 to 0.55. If the specific viscosity is less than 0.12, the molded product may become brittle. If the specific viscosity is higher than 0.55, the melt viscosity of the resin may increase, resulting in poor moldability.

[0071] (Impact modifier (C)) The resin composition of the present invention contains an impact modifier (C). The impact modifier (C) is preferably a core-shell type polymer consisting of a core which is a rubber-like polymer and a shell obtained by graft polymerization to the rubber-like polymer. By using a core-shell type polymer, the dispersibility in polycarbonate becomes good, and high impact strength tends to be obtained.

[0072] The average particle size of the impact modifier (C) is preferably 10 nm or more. More preferably, it is 30 nm or more, and even more preferably, it is 50 nm or more. If the average particle size is less than 10 nm, sufficient impact strength tends not to be obtained. The average particle size is measured in the latex state of the rubber-like polymer and the graft copolymer. The volume average particle size was measured using a MICROTRAC UPA150 manufactured by Nikkiso Co., Ltd. as a measuring device.

[0073] The rubbery polymer corresponding to the core of the impact resistance modifier (C) is a rubbery polymer of a vinyl monomer, or a polymer of a diene monomer and a vinyl monomer, and it is preferable that the vinyl monomer is at least one selected from the group consisting of a (meth)acrylic acid monomer and a (meth)acrylic acid alkyl ester monomer, from the viewpoint of improving the impact resistance of the resin composition of the present invention and also from the viewpoint of raw material costs.

[0074] The (meth)acrylic acid monomer refers to an acrylic acid monomer, a methacrylic acid monomer, or a mixture thereof. The (meth)acrylic acid alkyl ester monomer refers to an acrylic acid alkyl ester monomer, a methacrylic acid alkyl ester monomer, or a mixture thereof.

[0075] A specific example of the diene monomer is 1,3-butadiene. Specific examples of the (meth)acrylic acid monomer and the (meth)acrylic acid alkyl ester monomer are acrylic acid, methacrylic acid, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, 2-hydroxyethyl methacrylate, and glycidyl methacrylate. Polymers obtained from such monomers include, for example, butadiene-acrylic acid ester copolymers.

[0076] The glass transition temperature (Tg) of the rubber-like polymer is preferably 0° C. or lower from the viewpoint of improving impact resistance, more preferably −20° C. or lower, and further preferably −40° C. or lower.

[0077] The shell portion of the impact resistance modifier (C) is at least one vinyl monomer, and can be formed by graft polymerization with at least one vinyl monomer.

[0078] Examples of vinyl monomers include aromatic vinyl compounds, vinyl cyanide compounds, unsaturated carboxylic acids, and unsaturated carboxylic acid esters. Among aromatic vinyl compounds, styrene and α-methylstyrene are preferred, among vinyl cyanide compounds, acrylonitrile and methacrylonitrile are preferred, and among unsaturated carboxylic acids and unsaturated carboxylic acid esters, acrylic acid, methacrylic acid, acrylic acid esters and methacrylic acid esters having alkyl esters with 1 to 12 carbon atoms are preferred. Since they have excellent dispersibility in polycarbonate resins and the resulting resin composition has excellent transparency, it is preferred that the vinyl monomer used in graft polymerization is an unsaturated carboxylic acid ester, or a mixture of an unsaturated carboxylic acid ester and an aromatic vinyl compound.

[0079] Furthermore, one or more reactive groups selected from epoxy groups, hydroxy groups, carboxy groups, alkoxy groups, isocyanate groups, acid anhydride groups, and acid chloride groups can be introduced into the graft portion of the impact modifier (C), which may improve dispersibility and impact resistance compared to the case of using a rubber graft copolymer that does not contain reactive groups.

[0080] The impact modifier (C) used in the present invention can be made transparent by using one having a refractive index of 1.485 or more and 1.495 or less. In this case, the refractive index is preferably 1.487 or more and 1.494 or less, more preferably 1.490 or more and 1.493 or less.

[0081] The impact modifier (C) may be produced by any of bulk polymerization, solution polymerization, suspension polymerization, and emulsion polymerization, but emulsion polymerization, i.e., emulsion graft polymerization, is preferred. Specifically, latex is added to a reaction vessel equipped with a stirrer, and then vinyl monomers, polymerization initiator, and water are added, and a chain transfer agent and an oxidation-reduction agent are added as necessary, followed by heating and stirring.

[0082] The types of polymerization initiator, chain transfer agent, and redox agent used here are not particularly limited, and known ones can be used. The method of adding each raw material to a reaction vessel is also not particularly limited, and they may be added all at once before the start of polymerization, or may be added in portions. The graft polymerization is carried out in one or more stages, and the monomer composition in each stage may be the same or different. The monomers may be added all at once, continuously, or in a combination of these.

[0083] When the emulsion polymerization method is employed, known polymerization initiators can be used, i.e., thermal decomposition type polymerization initiators such as 2,2'-azobisisobutyronitrile, hydrogen peroxide, potassium persulfate, and ammonium persulfate. In addition, t-butylperoxyisopropyl carbonate, paramenthane hydroperoxide, cumene hydroperoxide, dicumyl peroxide, t-butyl hydroperoxide, di-t-butyl peroxide, t-hexyl peroxide, and the like can be used. It can also be used as a redox type polymerization initiator in which a peroxide such as an organic peroxide such as silperoxide, or an inorganic peroxide such as hydrogen peroxide, potassium persulfate, or ammonium persulfate is used in combination with a reducing agent such as sodium formaldehyde sulfoxylate or glucose, if necessary, a transition metal salt such as iron (II) sulfate, if necessary, a chelating agent such as disodium ethylenediaminetetraacetate, if necessary, and a phosphorus-based flame retardant such as sodium pyrophosphate, if necessary, and the like.

[0084] When a redox type polymerization initiator system is used, the polymerization can be carried out even at a low temperature where the peroxide does not substantially decompose thermally, so that the polymerization temperature can be set in a wide range, which is preferable. Among them, it is preferable to use an aromatic ring-containing peroxide such as cumene hydroperoxide or dicumyl peroxide as the redox type polymerization initiator. The amount of the polymerization initiator used, and the amount of the reducing agent, transition metal salt, chelating agent, etc. used when a redox type polymerization initiator is used can be within a known range.

[0085] When synthesizing the impact resistance modifier (C) by emulsion polymerization, as the polymerization emulsifier, a conventionally known polymerization emulsifier can be used, such as an alkali metal salt of a higher fatty acid, such as disproportionated rosin acid, oleic acid, or stearic acid, or an alkali metal salt of a phosphoric acid compound, or further an alkali metal salt of a sulfonic acid or a sulfuric acid compound.

[0086] When the impact modifier (C) is obtained by emulsion polymerization, for example, the latex of the impact modifier (C) is mixed with an acid such as hydrochloric acid or a divalent or higher metal salt such as calcium chloride, magnesium chloride, magnesium sulfate, aluminum chloride, calcium acetate, etc. to coagulate, and then heat treatment, dehydration, washing, and drying are performed according to a known method to separate the impact modifier from the aqueous medium (also called coagulation method). Alternatively, a water-soluble organic solvent such as alcohol such as methanol, ethanol, propanol, or acetone is added to the latex to precipitate the impact modifier, and the solvent is separated by centrifugation or filtration, and then the impact modifier is dried and isolated. Another method is to add an organic solvent having a small water solubility such as methyl ethyl ketone to the latex containing the impact modifier used in the present invention to extract the impact modifier component in the latex into the organic solvent layer, and after separating the organic solvent layer, the organic solvent layer is mixed with water or the like to precipitate the impact modifier component. Alternatively, the latex can be directly powdered by a spray drying method.

[0087] In the present invention, the resin composition may be one in which the impact modifier (C) is previously contained in the acrylic resin (B) and then contained in the polycarbonate resin. Specific examples of the acrylic resin containing the impact modifier include, but are not limited to, the following.

[0088] Examples of such resins include trade names ACRYPET IRK304, IRL309, and VRL40 manufactured by Mitsubishi Chemical Corporation, trade names PARAPET GR00100, GR04970, and GR-H60 manufactured by Kuraray Co., Ltd., trade names PLEXIGLAS AG100 and zk6HF manufactured by Daicel-Evonik Ltd., and trade names DELPET SR8350 and SR8500 manufactured by Asahi Kasei Corporation.

[0089] (Ion pair compound (D)) The ion pair compound used in the present invention is used as an antistatic agent, has a melting point of 100°C or lower, a 10% weight loss temperature measured by TG-TDA of 250°C or higher, and satisfies the following formula [I]: R I >R D -30[I] (In the formula, R I is the contact angle (°) of a water droplet of a resin composition having an ion pair compound content of 2 parts by weight per 100 parts by weight of polycarbonate resin, and R D is the contact angle of a water droplet on polycarbonate resin (°).

[0090] The necessity for the melting point of the ion pair compound to be 100°C or less is explained below. It is known that an ion pair compound with a low melting point, particularly one that is liquid at room temperature, can be added to a resin to give the resin composition antistatic properties. The reason for this is that an ion pair compound with a low melting point has an organic compound portion with a certain size, which weakens the Coulomb force between positive and negative charges and increases the affinity with the matrix resin, and is therefore thought to be dispersed appropriately in the resin composition to exhibit antistatic properties. In particular, when considering addition to a polycarbonate resin, a compound with a melting point of 100°C or less is suitable for imparting good antistatic properties. On the other hand, an ion pair compound with a melting point of more than 100°C has a strong Coulomb force or a small organic compound portion with low affinity with the resin, so it is difficult to disperse in the aromatic polycarbonate resin and does not exhibit good antistatic properties. The melting point of the ion pair compound is preferably 90°C or less.

[0091] The necessity for the 10% weight loss temperature measured by TG-TDA to be 250°C or higher is explained below. If this temperature is low, the ion-pair compound is more likely to thermally decompose in environments where the resin compound is exposed to high temperatures, such as melt kneading and injection molding, and the compounds generated by this thermal decomposition also contribute to the thermal decomposition of the resin polymer, causing problems such as molding instability and reduced mechanical properties due to a decrease in molecular weight. The 10% weight loss temperature of the ion-pair compound measured by TG-TDA is preferably 260°C or higher, and more preferably 270°C or higher.

[0092] The reason why formula [1] should be satisfied is explained below. The more hydrophobic the ion pair compound is, the more the ion pair compound is prevented from dissolving in water when the resin composition containing the ion pair compound comes into contact with water, and the more the sustained antistatic property is improved. The degree of hydrophobicity of the ion pair compound can be defined by the contact angle of a water droplet with the resin composition to which the ion pair compound is added. If formula [I] is not satisfied, this means that the ion pair compound is more hydrophilic, and the more the ion pair compound dissolves in water when the resin composition comes into contact with water, and sustained antistatic property cannot be ensured. Furthermore, in order to ensure better sustained antistatic property, it is more preferable that the following formula [II] is satisfied. R I >R D -20[II] (In the formula, R I is the contact angle (°) of a water droplet of a resin composition having an ion pair compound content of 2 parts by weight per 100 parts by weight of polycarbonate resin, and R D is the contact angle of a water droplet on polycarbonate resin (°).

[0093] The ion pair compound having a melting point of 100°C or lower, a 10% weight loss temperature measured by TG-TDA of 250°C or higher, and satisfying formula [1] preferably contains an organic ammonium ion or an organic phosphonium ion represented by the following formula (3) as a cation, or a sulfonylimide ion represented by the following formula (4) or a fluorosulfonate ion represented by the following formula (5) as an anion.

[0094] [ka] [In the formula, R1 and R2 represent a hydrocarbon group, and M represents a N atom or a P atom.]

[0095] [ka] [In the formula, R3 and R4 each represent a perfluoroalkyl group.]

[0096] [ka] [In the formula, R5 represents a perfluoroalkyl group.]

[0097] In addition, in formula (3), M is preferably a P atom, R1 is preferably an alkyl group having 1 or more carbon atoms, and R2 is preferably an alkyl group having 4 or more carbon atoms. Furthermore, it is more preferable that R1 is an alkyl group having 4 or more carbon atoms, and R2 is more preferably an alkyl group having 12 or more carbon atoms. It is preferable that R1 is an alkyl group having 10 or less carbon atoms, and R2 is an alkyl group having 20 or less carbon atoms.

[0098] In formula (4), R3 and R4 are each preferably a perfluoroalkyl group having 1 to 4 carbon atoms, more preferably a trifluoromethyl group, and in formula (5), R5 is preferably a perfluoroalkyl group having 1 to 4 carbon atoms, more preferably a perfluorobutyl group.

[0099] (Method for producing a resin composition containing a polycarbonate resin, an acrylic resin, an impact modifier, and an ion pair compound) The resin composition of the present invention is preferably prepared by blending a polycarbonate resin, an acrylic resin, an impact modifier and an antistatic agent in a molten state. As a method for blending in a molten state, an extruder is generally used, and the molten resin is kneaded at a temperature of 200 to 320°C, preferably 220 to 300°C, more preferably 230 to 290°C, and pelletized. This provides pellets of a resin composition in which both resins are uniformly blended. The configuration of the extruder, the configuration of the screw, etc. are not particularly limited. If the molten resin temperature in the extruder exceeds 320°C, the resin may become discolored or may undergo thermal decomposition. On the other hand, if the resin temperature is below 200°C, the resin viscosity may be too high and the extruder may be overloaded.

[0100] (weight ratio) The weight ratio of the polycarbonate resin (A) and the acrylic resin (B) used in the present invention is preferably in the range of 30:70 to 99:1. It is more preferably in the range of 35:65 to 95:5, even more preferably in the range of 40:60 to 93:7, particularly preferably in the range of 45:55 to 92:8, and most preferably in the range of 50:50 to 90:10. By keeping it in the above range, a resin composition having superior surface hardness and impact resistance can be obtained.

[0101] The impact modifier (C) used in the present invention is blended in the range of 5 to 60 parts by weight per 100 parts by weight of the total of the polycarbonate resin and the acrylic resin. The range is preferably 7 to 55 parts by weight, more preferably 8 to 50 parts by weight, even more preferably 9 to 48 parts by weight, and particularly preferably 10 to 45 parts by weight. By adjusting the range to the above range, a resin composition excellent in surface hardness and impact resistance can be obtained.

[0102] The ion pair compound (D) used in the present invention is contained in the range of 0.1 to 10 parts by weight relative to 100 parts by weight in total of the polycarbonate resin and the acrylic resin. The range is preferably 0.3 to 8 parts by weight, more preferably 0.5 to 7 parts by weight, and even more preferably 1 to 6 parts by weight. By setting the range as above, a resin composition excellent in thermal stability, surface hardness, impact resistance, and sustained antistatic properties can be obtained.

[0103] (Additives) The resin composition of the present invention may contain additives such as heat stabilizers, plasticizers, light stabilizers, polymerized metal deactivators, flame retardants, lubricants, surfactants, antibacterial agents, ultraviolet absorbers, release agents, and colorants depending on the application and need. Additives can be added.

[0104] (Heat stabilizer) The resin composition of the present invention preferably contains a heat stabilizer in particular in order to suppress the decrease in molecular weight and the deterioration of color during extrusion and molding. Examples of the heat stabilizer include phosphorus-based heat stabilizers, phenol-based heat stabilizers, and sulfur-based heat stabilizers, and these can be used alone or in combination of two or more. It is preferable to blend a phosphite compound as the phosphorus-based stabilizer. Examples of the phosphite compound include pentaerythritol-type phosphite compounds, phosphite compounds that react with dihydric phenols and have a cyclic structure, and phosphite compounds having other structures.

[0105] Specific examples of the pentaerythritol phosphite compound include distearyl pentaerythritol diphosphite, bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite, bis(2,6-di-tert-butyl-4-ethylphenyl)pentaerythritol diphosphite, phenyl bisphenol A pentaerythritol diphosphite, bis(nonylphenyl)pentaerythritol diphosphite, dicyclohexyl pentaerythritol diphosphite, and the like. Among these, distearyl pentaerythritol diphosphite and bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite are preferred.

[0106] Examples of the phosphite compounds having a cyclic structure that react with the above dihydric phenols include 2,2'-methylenebis(4,6-di-tert-butylphenyl)(2,4-di-tert-butylphenyl)phosphite, 2,2'-methylenebis(4,6-di-tert-butylphenyl)(2-tert-butyl-4-methylphenyl)phosphite, 2,2'-methylenebis(4-methyl-6-tert-butylphenyl)(2-tert-butyl-4-methylphenyl)phosphite, phosphite, 2,2'-ethylidenebis(4-methyl-6-tert-butylphenyl)(2-tert-butyl-4-methylphenyl)phosphite, 2,2'-methylene-bis-(4,6-di-t-butylphenyl)octylphosphite, 6-tert-butyl-4-[3-[(2,4,8,10)-tetra-tert-butyldibenzo[d,f][1,3,2]dioxaphosphepin-6-yl)oxy]propyl]-2-methylphenol, and the like.

[0107] Examples of phosphite compounds having the above other structures include triphenyl phosphite, tris(nonylphenyl)phosphite, tridecyl phosphite, trioctyl phosphite, trioctadecyl phosphite, didecyl monophenyl phosphite, dioctyl monophenyl phosphite, diisopropyl monophenyl phosphite, monobutyl diphenyl phosphite, monodecyl diphenyl phosphite, monooctyl diphenyl phosphite, 2,2-methylenebis(4,6-di-tert-butylphenyl)octyl phosphite, tris(diethylphenyl)phosphite, tris(di-isopropylphenyl)phosphite, tris(di-n-butylphenyl)phosphite, tris(2,4-di-tert-butylphenyl)phosphite, and tris(2,6-di-tert-butylphenyl)phosphite.

[0108] In addition to the various phosphite compounds, examples of the compounds include phosphate compounds, phosphonite compounds, and phosphonate compounds.

[0109] The phosphate compounds include tributyl phosphate, trimethyl phosphate, tricresyl phosphate, triphenyl phosphate, and trichlorophenyl phosphate. , triethyl phosphate, diphenyl cresyl phosphate, diphenyl monoorthoxenyl phosphate, tributoxyethyl phosphate, dibutyl phosphate, dioctyl phosphate, diisopropyl phosphate, etc., and preferred are triphenyl phosphate and trimethyl phosphate.

[0110] Examples of the phosphonite compounds include tetrakis(2,4-di-tert-butylphenyl)-4,4'-biphenylene diphosphonite, tetrakis(2,4-di-tert-butylphenyl)-4,3'-biphenylene diphosphonite, tetrakis(2,4-di-tert-butylphenyl)-3,3'-biphenylene diphosphonite, tetrakis(2,6-di-tert-butylphenyl)-4,4'-biphenylene diphosphonite, tetrakis(2,6-di-tert-butylphenyl)-4,3'-biphenylene diphosphonite, tetrakis(2,6-di-tert-butylphenyl)-3,3'-biphenylene diphosphonite, bis(2,4-di-tert-butylphenyl)-4-phenyl-phenylphosphonite, bis Examples of the phosphonite include (2,4-di-tert-butylphenyl)-3-phenyl-phenylphosphonite, bis(2,6-di-n-butylphenyl)-3-phenyl-phenylphosphonite, bis(2,6-di-tert-butylphenyl)-4-phenyl-phenylphosphonite, and bis(2,6-di-tert-butylphenyl)-3-phenyl-phenylphosphonite. Tetrakis(di-tert-butylphenyl)-biphenylene diphosphonite and bis(di-tert-butylphenyl)-phenyl-phenylphosphonite are preferred, and tetrakis(2,4-di-tert-butylphenyl)-biphenylene diphosphonite and bis(2,4-di-tert-butylphenyl)-phenyl-phenylphosphonite are more preferred. Such phosphonite compounds can be used in combination with the phosphite compounds having an aryl group substituted with two or more alkyl groups, and are therefore preferred.

[0111] Examples of the phosphonate compound include dimethyl benzenephosphonate, diethyl benzenephosphonate, and dipropyl benzenephosphonate.

[0112] Among the above phosphorus-based heat stabilizers, trisnonylphenyl phosphite, trimethyl phosphate, tris(2,4-di-tert-butylphenyl)phosphite, bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, and bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite are preferably used.

[0113] The phosphorus-based heat stabilizers can be used alone or in combination of two or more kinds. The phosphorus-based heat stabilizer is preferably blended in an amount of 0.001 to 1 part by weight, more preferably 0.01 to 0.5 parts by weight, and even more preferably 0.01 to 0.3 parts by weight per 100 parts by weight of the resin composition.

[0114] In order to suppress the decrease in molecular weight and deterioration of color during extrusion and molding, the resin composition used in the present invention may also contain a heat stabilizer such as a hindered phenol-based heat stabilizer or a sulfur-based heat stabilizer in combination with a phosphorus-based heat stabilizer.

[0115] The hindered phenol-based heat stabilizer is not particularly limited as long as it has an antioxidant function. Examples of the hindered phenol-based heat stabilizer include n-octadecyl-3-(4'-hydroxy-3',5'-di-t-butylphenyl)propionate, tetrakis{methylene-3-(3',5'-di-t-butyl-4-hydroxyphenyl)propionate}methane, distearyl(4-hydroxy-3-methyl-5-t-butylbenzyl)malonate, triethylene glycol-bis{3-(3-t-butyl-5-methyl-4-hydroxyphenyl)propionate}, 1,6-hexanediol-bis{3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate}, pentaerythrityl-tetrakis{3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate}, 2,2- Thiodiethylene bis{3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate}, 2,2-thiobis(4-methyl-6-t-butylphenol), 1,3,5-trimethyl-2,4,6-tris(3,5-di-t-butyl-4-hydroxybenzyl)benzene, tris(3,5-di-t-butyl-4-hydroxybenzyl)isocyanurate, 2,4-bis{(octyl thio)methyl}-o-cresol, isooctyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, 2,5,7,8-tetramethyl-2(4',8',12'-trimethyltridecyl)chroman-6-ol, 3,3',3",5,5',5"-hexa-t-butyl-a,a',a"-(mesitylene-2,4,6-triyl)tri-p-cresol, and the like.

[0116] Among these, n-octadecyl-3-(4'-hydroxy-3',5'-di-t-butylphenyl)propionate, pentaerythrityl-tetrakis{3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate}, 3,3',3",5,5',5"-hexa-t-butyl-a,a',a'-(mesitylene-2,4,6-triyl)tri-p-cresol, 2,2-thiodiethylenebis{3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate}, and the like are preferred.

[0117] These hindered phenol-based heat stabilizers may be used alone or in combination of two or more.

[0118] The hindered phenol-based heat stabilizer is preferably blended in an amount of 0.001 to 1 part by weight, more preferably 0.01 to 0.5 parts by weight, and even more preferably 0.01 to 0.3 parts by weight, per 100 parts by weight of the resin composition.

[0119] Examples of sulfur-based heat stabilizers include dilauryl-3,3'-thiodipropionate, ditridecyl-3,3'-thiodipropionate, dimyristyl-3,3'-thiodipropionate, distearyl-3,3'-thiodipropionate, laurylstearyl-3,3'-thiodipropionate, pentaerythritol tetrakis (3-laurylthiopropionate), bis [2-methyl-4- (3-laurylthiopropionyloxy) -5-tert-butylphenyl] sulfide, octadecyl disulfide, mercaptobenzimidazole, 2-mercapto-6-methylbenzimidazole, 1,1'-thiobis (2-naphthol), etc. Among the above, pentaerythritol tetrakis (3-laurylthiopropionate) is preferred.

[0120] These sulfur-based heat stabilizers may be used alone or in combination of two or more kinds.

[0121] The sulfur-based heat stabilizer is preferably blended in an amount of 0.001 to 1 part by weight, more preferably 0.01 to 0.5 parts by weight, and even more preferably 0.01 to 0.3 parts by weight, per 100 parts by weight of the resin composition.

[0122] When a phosphite-based heat stabilizer, a phenol-based heat stabilizer, and a sulfur-based heat stabilizer are used in combination, the total amount of these is preferably 0.001 to 1 part by weight, more preferably 0.01 to 0.3 part by weight, per 100 parts by weight of the resin composition.

[0123] (Release agent) In order to further improve the releasability from a mold during melt molding, the resin composition of the present invention may contain a mold release agent within a range that does not impair the object of the present invention.

[0124] Examples of such release agents include higher fatty acid esters of monohydric or polyhydric alcohols, higher fatty acids, paraffin wax, beeswax, olefin waxes, olefin waxes containing carboxy groups and / or carboxylic anhydride groups, silicone oils, and organopolysiloxanes.

[0125] The higher fatty acid ester is preferably a partial or full ester of a monohydric or polyhydric alcohol having 1 to 20 carbon atoms and a saturated fatty acid having 10 to 30 carbon atoms. Examples of such partial or full esters of a monohydric or polyhydric alcohol and a saturated fatty acid include stearic acid monoglyceride, stearic acid diglyceride, stearic acid triglyceride, stearic acid monosorbitate, stearyl stearate, behenic acid monoglyceride, behenyl behenate, pentaerythritol monostearate, pentaerythritol tetrastearate, pentaerythritol tetrapelargonate, propylene glycol monostearate, stearyl stearate, palmityl palmitate, butyl stearate, methyl laurate, isopropyl palmitate, biphenyl biphenate, sorbitan monostearate, and 2-ethylhexyl stearate.

[0126] Of these, stearic acid monoglyceride, stearic acid triglyceride, pentaerythritol tetrastearate, and behenyl behenate are preferably used.

[0127] The higher fatty acid is preferably a saturated fatty acid having a carbon number of 10 to 30. Examples of such fatty acids include myristic acid, lauric acid, palmitic acid, stearic acid, and behenic acid.

[0128] These release agents may be used alone or in combination of two or more. The amount of such release agent to be added is preferably 0.01 to 5 parts by weight based on 100 parts by weight of the resin composition.

[0129] (UV absorber) The resin composition of the present invention may contain an ultraviolet absorber. Examples of the ultraviolet absorber include benzotriazole-based ultraviolet absorbers, benzophenone-based ultraviolet absorbers, triazine-based ultraviolet absorbers, cyclic iminoester-based ultraviolet absorbers, and cyanoacrylate-based ultraviolet absorbers, and among these, benzotriazole-based ultraviolet absorbers are preferred.

[0130] Examples of the benzotriazole-based ultraviolet absorbers include 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-5'-tert-butylphenyl)benzotriazole, 2-(2'-hydroxy-5'-tert-octylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-tert-amylphenyl)benzotriazole, 2-(2'-hydroxy-3'-dodecyl-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-bis(α,α'-dimethylbenzyl)phenylbenzotriazole, 2-[2'-hydroxy benzotriazole-based ultraviolet absorbers represented by 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-5-chlorobenzotriazole, 2,2'methylenebis[4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazol-2-yl)phenol], and methyl-3-[3-tert-butyl-5-(2H-benzotriazol-2-yl)-4-hydroxyphenylpropionate-polyethylene glycol condensate can be mentioned.

[0131] The proportion of such an ultraviolet absorber is preferably 0.01 to 2 parts by weight, more preferably 0.1 to 1 part by weight, and further preferably 0.2 to 0.5 parts by weight, based on 100 parts by weight of the resin composition.

[0132] (Light stabilizer) The resin composition of the present invention may contain a light stabilizer. The inclusion of a light stabilizer has the advantages of being excellent in terms of weather resistance and making it difficult for cracks to occur in a molded product.

[0133] Examples of the light stabilizer include 1,2,2,6,6-pentamethyl-4-piperidyl methacrylate, didecanoic acid bis(2,2,6,6-tetramethyl-1-octyloxy-4-piperidinyl) ester, bis(1,2,2,6,6-pentamethyl-4-piperidinyl)-[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]butyl malonate, 2,4-bis[N-butyl-N-(1-cyclohexyloxy-2,2,6,6 -tetramethylpiperidin-2-yl)amino]-6-(2-hydroxyethylamine)-1,3,5-triazine, bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate, methyl(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate, bis(2,2,6,6-tetramethyl-4-piperidyl) carbonate, bis(2,2,6,6-tetramethyl-4-piperidyl) succinate, bis(2,2,6,6-tetramethyl 4-benzoyloxy-2,2,6,6-tetramethylpiperidine, 4-octanoyloxy-2,2,6,6-tetramethylpiperidine, bis(2,2,6,6-tetramethyl-4-piperidyl)diphenylmethane-p,p′-dicarbamate, bis(2,2,6,6-tetramethyl-4-piperidyl)benzene-1,3-disulfonate, bis(2,2,6,6-tetramethyl-4-piperidyl)phenylphosphine Examples of the light stabilizer include hindered amines such as thiophene, nickel bis(octylphenyl sulfide), nickel complex-3,5-di-t-butyl-4-hydroxybenzyl phosphate monoethylate, and nickel complexes such as nickel dibutyldithiocarbamate. These light stabilizers may be used alone or in combination of two or more. The content of the light stabilizer is preferably 0.001 to 1 part by weight, and more preferably 0.01 to 0.5 parts by weight, based on 100 parts by weight of the resin composition.

[0134] (Epoxy stabilizer) In order to improve hydrolysis resistance, an epoxy compound may be blended into the resin composition of the present invention within the range not impairing the object of the present invention.

[0135] Epoxy stabilizers include epoxidized soybean oil, epoxidized linseed oil, phenyl glycidyl ether, allyl glycidyl ether, t-butylphenyl glycidyl ether, 3,4-epoxycyclohexylmethyl-3',4'-epoxycyclohexyl carboxylate, 3,4-epoxy-6-methylcyclohexylmethyl-3',4'-epoxy-6'-methylcyclohexyl carboxylate, 2,3-epoxycyclohexylmethyl-3',4'-epoxycyclohexyl carboxylate, 4-(3,4-epoxy-5-methylcyclohexyl) ... butyl-3',4'-epoxycyclohexyl carboxylate, 3,4-epoxycyclohexylethylene oxide, cyclohexylmethyl-3,4-epoxycyclohexyl carboxylate, 3,4-epoxy-6-methylcyclohexylmethyl-6'-methylcyclohexyl carboxylate, bisphenol A diglycidyl ether, tetrabromobisphenol A glycidyl ether, diglycidyl ester of phthalic acid, diglycidyl ester of hexahydrophthalic acid, bis-epoxydicyclopentadienyl ether, bis-epoxyethylene ethylene glycol, bis-epoxycyclohexyl adipate, butadiene diepoxide, tetraphenylethylene epoxide, octyl epoxy thalate, epoxidized polybutadiene, 3,4-dimethyl-1,2-epoxycyclohexane, 3,5-dimethyl-1,2-epoxycyclohexane, 3-methyl-5-t-butyl-1,2-epoxycyclohexane, octadecyl-2,2-dimethyl-3,4-epoxycyclohexyl carboxylate, N-butyl-2,2-dimethyl-3,4-epoxycyclohexyl carboxylate, cyclohexyl- 2-Methyl-3,4-epoxycyclohexyl carboxylate, N-butyl-2-isopropyl-3,4-epoxy-5-methylcyclohexyl carboxylate, octadecyl-3,4-epoxycyclohexyl carboxylate, 2-ethylhexyl-3',4'-epoxycyclohexyl carboxylate, 4,6-dimethyl-2,3-epoxycyclohexyl-3',4'-epoxycyclohexyl carboxylate, 4,5-epoxy tetrahydrophthalic anhydride, 3-t-butyl-4,5-epoxy tetrahydrophthalic anhydride, diethyl-4,5-epoxy-cis-1,2-cyclohexyl dicarboxylate, di-n-butyl-3-t-butyl-4,5-epoxy-cis-1,2-cyclohexyl dicarboxylate, etc. Bisphenol A diglycidyl ether is preferred from the viewpoint of compatibility, etc.

[0136] Such an epoxy stabilizer is desirably blended in an amount of 0.0001 to 5 parts by weight, preferably 0.001 to 1 part by weight, and more preferably 0.005 to 0.5 parts by weight, relative to 100 parts by weight of the resin composition.

[0137] (Bluing agent) The resin composition of the present invention can be blended with a bluing agent to eliminate the yellow color of the lens due to the polymer or ultraviolet absorbing agent. As the bluing agent, any agent that is used for polycarbonate can be used without any problem. In general, anthraquinone dyes are easily available and are preferred.

[0138] Specific examples of bluing agents include those having the general name Solvent Violet 13 [CA. No (Color Index No) 60725], those having the general name Solvent Violet 31 [CA. No 68210, those having the general name Solvent Violet 33 [CA. No 60725], those having the general name Solvent Blue 94 [CA. No 61500], those having the general name Solvent Violet 36 [CA. No 68210], those having the general name Solvent Blue 97 [Bayer's "Macrolex Violet RR"], and those having the general name Solvent Blue 45 [CA. No 61110].

[0139] These bluing agents may be used alone or in combination of two or more. The bluing agent is preferably used in an amount of 0.1×10 -4 ~2×10 -4 It is mixed in parts by weight.

[0140] (Flame retardant) A flame retardant can also be blended into the resin composition of the present invention. Examples of the flame retardant include halogen-based flame retardants such as brominated epoxy resin, brominated polystyrene, brominated polycarbonate, brominated polyacrylate, and chlorinated polyethylene, phosphate ester-based flame retardants such as monophosphate compounds and phosphate oligomer compounds, organic phosphorus-based flame retardants other than phosphate ester-based flame retardants such as phosphinate compounds, phosphonate compounds, phosphonitrile oligomer compounds, and phosphonic acid amide compounds, organic metal salt-based flame retardants such as organic sulfonic acid alkali (earth) metal salts, boric acid metal salt-based flame retardants, and stannic acid metal salt-based flame retardants, as well as silicone-based flame retardants, ammonium polyphosphate-based flame retardants, and triazine-based flame retardants. In addition, a flame retardant assistant (e.g., sodium antimonate, antimony trioxide, etc.) and a dripping inhibitor (polytetrafluoroethylene having fibril forming ability, etc.) may be blended and used in combination with the flame retardant.

[0141] Among the above-mentioned flame retardants, compounds that do not contain chlorine atoms or bromine atoms are more suitable as flame retardants for the molded article of the present invention, which is also characterized by reduced environmental impact, since they reduce factors that are considered undesirable when incinerating or thermally recycling the compounds.

[0142] When a flame retardant is added, the amount is preferably in the range of 0.05 to 50 parts by weight per 100 parts by weight of the resin composition. When the amount is 0.05 part by weight or more, sufficient flame retardancy is easily achieved, and when the amount is 50 parts by weight or less, the strength and heat resistance of the molded product are excellent.

[0143] (molded product) The resin composition of the present invention can be molded and processed into a molded product (including a sheet or film) by any method such as injection molding, compression molding, injection compression molding, melt film forming, or casting, and can be used as a molded product such as an optical lens, an optical disk, an optical film, a plastic substrate, an optical card, a liquid crystal panel, a headlamp lens, a light guide plate, a diffusion plate, a protective film, an OPC binder, a front plate, a housing, a tray, a water tank, a lighting cover, a signboard, a plastic window, etc. In particular, it can be used as a member requiring high surface hardness such as a front plate, a housing, a tray, a water tank, a lighting cover, a signboard, or a plastic window.

[0144] (Impact strength) The resin composition of the present invention has a Charpy notched impact strength of 10 kJ / m, measured according to ISO 179. 2 It is preferable that the concentration is 11 kJ / m or more. 2 More preferably, it is 12 kJ / m or more. 2 More preferably, it is 13 kJ / m or more. 2 It is particularly preferable that the notched Charpy impact strength is 100 kJ / m or more. 2 The following functions are sufficient.

[0145] (Pencil hardness) The resin composition of the present invention preferably has a pencil hardness of H or more. From the viewpoint of being more excellent in scratch resistance, it is more preferable that the pencil hardness is 2H or more. A pencil hardness of 4H or less provides sufficient functionality. The pencil hardness can be increased by increasing the weight ratio of the acrylic resin. In the present invention, the pencil hardness refers to a hardness at which no scratch marks are left when the resin composition of the present invention is rubbed with a pencil having a specific pencil hardness, and is defined as a hardness of JIS It is preferable to use the pencil hardness used in the surface hardness test of a coating film, which can be measured according to K-5600, as an index. Pencil hardness decreases in the following order: 9H, 8H, 7H, 6H, 5H, 4H, 3H, 2H, H, F, HB, B, 2B, 3B, 4B, 5B, 6B, with the hardest being 9H and the softest being 6B.

[0146] (Antistatic) The resin composition of the present invention has a surface resistivity of 1×10 15 It is preferable that the resistance is Ω / □ or less, and 1×10 14 It is more preferable that the resistance is 1×10 13 It is more preferable that the resistance is Ω / □ or less.

[0147] (Surface treatment) Molded articles formed from the resin composition of the present invention can be subjected to various surface treatments. The surface treatment referred to here is a method for forming a new layer on the surface of a resin molded article, such as vapor deposition (physical vapor deposition, chemical vapor deposition, etc.), plating (electroplating, electroless plating, hot-dip plating, etc.), painting, coating, printing, etc., and any commonly used method can be applied. Specific examples of the surface treatment include various surface treatments such as hard coating, water-repellent / oil-repellent coating, ultraviolet absorbing coating, infrared absorbing coating, and metallizing (vapor deposition, etc.). Hard coating is a particularly preferred and necessary surface treatment. EXAMPLES

[0148] The present invention will be described in detail below with reference to examples, but the present invention is not limited thereto. In the examples, "parts" means "parts by weight." The resins and evaluation methods used in the examples are as follows.

[0149] [Evaluation method] <Evaluation of polycarbonate resin> 1. Polymer composition ratio (NMR) Each repeating unit was measured by proton NMR using a JNM-AL400 manufactured by JEOL Ltd., and the polymer composition ratio (molar ratio) was calculated.

[0150] 2. Specific viscosity The viscosity was measured using an Ostwald viscometer from a solution of 0.7 g of polycarbonate resin dissolved in 100 ml of methylene chloride at 20°C. Specific viscosity (η SP )=(t-t0) / t0 [t0 is the number of seconds that methylene chloride falls, and t is the number of seconds that the sample solution falls]

[0151] <Evaluation of ion-pair compounds> 1. Melting Point Materials that are liquid at room temperature (20°C) are recorded as <20°C. Materials that are not liquid at room temperature are recorded as the melting point by reading the peak position corresponding to the melting point from a chart of heat quantity versus temperature obtained using a DSC analyzer (NETZSCH DSC214) at a heating rate of 10°C / min.

[0152] 2.Heat resistance The 10% weight loss temperature was measured using a TG-DTA analyzer (Thermo plus EVO2 manufactured by Rigaku) ​​under conditions of an air atmosphere and a heating rate of 20°C / min.

[0153] <Evaluation of Resin Composition> 1.Hydrophilicity of the molded product surface Using a contact angle measuring device (GI-1000 manufactured by Elma Sales Co., Ltd.), the water droplet contact angle (R D ) and the water droplet contact angle (R I ) was measured by dropping a drop of water onto a flat test piece obtained by injection molding.

[0154] 2. Antistatic properties (before wiping with water) A flat test piece of 45 mm x 50 mm x 2 mm was prepared by injection molding under the above conditions, and measurements were carried out under the following conditions. That is, the flat test piece was prepared at 23°C and 50% relative humidity for 48 hours or more, and then the surface resistivity was measured using a resistivity meter (high resistance resistivity meter MCP-HT450 manufactured by Mitsubishi Chemical Analic Corporation) at a measurement voltage of 1000 V. The smaller the value, the better the antistatic performance. When the surface resistivity was 1 x 10 14 Ω / □ or less: ◎, 1×10 14 Ω / □ greater than 1×10 15 Ω / □ or less: ○, 1×10 15If it was greater than Ω / □, it was marked as ×.

[0155] 3. Antistatic properties (after wiping with water) A 500g cylindrical weight was wrapped in a water-soaked Kimtowel (manufactured by Nippon Paper Crecia Co., Ltd.), placed on the flat test piece, and slid 10 times to wipe the surface with water. Next, the surface was lightly wiped 3 times with a dry Kimwipe to remove water droplets. The surface resistivity was then evaluated using the same method as in 2 above. When the surface resistivity was 1×10 14 Ω / □ or less: ◎, 1×10 14 Ω / □ greater than 1×10 15 Ω / □ or less: ○, 1×10 15 If it was greater than Ω / □, it was marked as ×.

[0156] 4.Thermal stability In injection molding, the resin was allowed to remain in the cylinder for 10 minutes, after which the viscosity average molecular weight (M1) of the injected molded product and the viscosity average molecular weight (M0) of the melt-kneaded pellets were measured. The cases where M0-M1≦1,000 was satisfied were marked with an ◯, and the cases where it was not satisfied were marked with an ×.

[0157] The viscosity average molecular weight in the present invention is determined by first calculating the specific viscosity (η SP ) was measured using an Ostwald viscometer from a solution of 0.7 g of polycarbonate resin in 100 ml of methylene chloride at 20°C, and the specific viscosity (η SP ) and the viscosity average molecular weight M was calculated from the following formulas [IV] and [V]. Specific viscosity (η SP )=(t-t0) / t0[III] [t0 is the number of seconds that methylene chloride falls, and t is the number of seconds that the sample solution falls] η SP / c=[η]+0.45×[η] 2 c (where [η] is the intrinsic viscosity) [IV] [η]=1.23×10 -4 M 0.83 [V]

[0158] 5.Surface hardness (pencil hardness) According to JIS K5400, a pencil was held at a 45 degree angle and a load of 750g was applied to the surface of the molded product in a thermostatic chamber at an atmospheric temperature of 23°C, and a line was drawn on the surface of the molded product with the pencil held at a 45 degree angle and the surface condition was visually evaluated. Pencil hardness of 2H or more was rated as ◎, H as ○, and F or less as ×.

[0159] 6. Notched Charpy impact strength The ISO bending test specimen obtained by the following method was subjected to measurement of notched Charpy impact strength according to ISO 179. 2 Above 10kJ / m 2 Anything less than this was marked as x.

[0160] [Resins and additives used] <Polycarbonate resin (A)> PC-1 (Example): Structural units derived from isosorbide (hereinafter ISS) / structural units derived from 3,9-bis(2-hydroxy-1,1-dimethylethyl)-2,4,8,10-tetraoxaspiro(5,5)undecane (hereinafter SPG) / structural units derived from 1,9-nonanediol (hereinafter ND) = 72 / 21 / 7 (mol %), specific viscosity 0.396 PC-2 (Example): Structural units derived from ISS / structural units derived from SPG / structural units derived from ND=58 / 38 / 4 (mol%), specific viscosity 0.425 PC-3 (comparative example): Structural units derived from ISS / structural units derived from ND=88 / 12 (mol%), specific viscosity 0.366

[0161] <Acrylic resin (B)> B-1 (Example): Acrypet VH001 manufactured by Mitsubishi Chemical Corporation (acrylic resin copolymerized with 95 mol % methyl methacrylate and 5 mol % methyl acrylate)

[0162] <Impact resistance modifier composite acrylic resin (B+C)> B+C (Example): Acrypet VRL40 manufactured by Mitsubishi Chemical Corporation

[0163] <Impact modifier (C)> C-1 (Example): Kane Ace M-230 manufactured by Kaneka Corporation C-2 (Example): Metablen W-377 manufactured by Mitsubishi Chemical Corporation C-3 (Example): Mitsubishi Chemical Corporation's Metablen E-870A

[0164] <Ion pair compound (D)> D-1: Trihexyl(tetradecyl)phosphonium bis(trifluoromethylsulfonyl)imide (Kanto Chemical Co., Ltd.) D-2: Tributyl(dodecyl)phosphonium bis(trifluoromethylsulfonyl)imide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) D-3: 1-ethyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl)imide (P12N111, manufactured by Mitsubishi Materials Corporation) D-4: 1-Ethylpyridinium bis(trifluoromethylsulfonyl)imide (EPYN111 manufactured by Mitsubishi Materials Corporation) D-5: 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide (EMIN111 manufactured by Mitsubishi Materials Corporation) D-6: 1-butyl-3-methylimidazolium perfluorobutanesulfonate (BMIEF41, manufactured by Mitsubishi Materials Corporation) D-7: 1-Butyl-3-methylimidazolium dicyanamide (Tokyo Chemical Industry Co., Ltd.) D-8 (Comparative Example): 1-Butyl-3-methylimidazolium chloride (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) D-9 (Comparative Example): Potassium perfluorobutanesulfonate (Megafac F-114P, Dai Nippon Ink and Chemicals, Inc.) D-10 (Comparative Example): Dodecylbenzenesulfonic acid tetrabutylphosphonium salt (DBS-P) (Takemoto Oil Co., Ltd.)

[0165] <Other ingredients> E: Surfactant type antistatic agent (non-ion pair) (Poem DL-100 manufactured by Riken Vitamin Co., Ltd.) F: A block polymer having a structure in which a polyamide block and a polyether block are ester-bonded (Pelestat NC6321, manufactured by Sanyo Chemical Industries, Ltd.)

[0166] [Reference Example 1] <Production of polycarbonate resin> 364 parts of isosorbide (hereinafter abbreviated as ISS), 221 parts of 3,9-bis(2-hydroxy-1,1-dimethylethyl)-2,4,8,10-tetraoxaspiro(5,5)undecane (hereinafter abbreviated as SPG), 39 parts of 1,9-nonanediol (hereinafter abbreviated as ND), 750 parts of diphenyl carbonate (hereinafter abbreviated as DPC), and 0.8×10 tetramethylammonium hydroxide as a catalyst. -2 parts and barium stearate 0.6 x 10 -4 The mixture was heated to 200°C in a nitrogen atmosphere and melted. The temperature was then raised to 220°C over 30 minutes, and the vacuum was adjusted to 20.0 kPa. The temperature was then raised to 240°C over a further 30 minutes, and the vacuum was adjusted to 10 kPa. After maintaining this temperature for 10 minutes, the vacuum was reduced to 133 Pa or less over 1 hour. After the reaction was completed, the mixture was discharged from the bottom of the reaction tank under nitrogen pressure, and while cooling in a water tank, it was cut with a pelletizer to obtain pellets (PC-1).

[0167] <Production of Resin Composition> Polycarbonate resin PC-1 and ion pair compound D-1 were mixed at a weight ratio of 100:2 and then fed to an extruder. A vented twin screw extruder with a diameter of 30 mm [Kobe Steel KTX-30] was used for extrusion, and pellets were obtained by melt kneading at a screw speed of 150 rpm, a discharge rate of 20 kg / h, and a vent vacuum of 3 kPa. The extrusion temperature was 250°C from the feed port to the die. A portion of the obtained pellets was dried in a hot air circulation dryer at 90°C for 6 hours or more, and then a three-stage plate (1 mmt, 2 mmt, 3 mmt) for evaluation was molded using an injection molding machine at a cylinder temperature of 250°C and a mold temperature of 70°C, and the hydrophilicity of the molded surface was evaluated by a water drop contact angle drop test. The evaluation results are shown in Table 1.

[0168] [Reference Examples 2 to 7] <Production of Resin Composition> Except for using polycarbonate resin PC-1 and ion pair compounds D-2 to D-7 and mixing them in a weight ratio of 100:2, the same operation as in Reference Example 1 was performed and the same evaluation was performed. Reference Example 2 corresponds to the case where ion pair compound D-2 was used, Reference Example 3 corresponds to the case where ion pair compound D-3 was used, Reference Example 4 corresponds to the case where ion pair compound D-4 was used, Reference Example 5 corresponds to the case where ion pair compound D-5 was used, Reference Example 6 corresponds to the case where ion pair compound D-6 was used, and Reference Example 7 corresponds to the case where ion pair compound D-7 was used. The evaluation results are shown in Table 1.

[0169] [Reference Comparative Examples 1 to 3] <Production of Resin Composition> Except for using polycarbonate resin PC-1 and ion pair compounds D-8 to D-10 and mixing them in a weight ratio of 100:2, the same operations as in Reference Example 1 were performed and the same evaluations were carried out. Reference Comparative Example 1 corresponds to the case where ion pair compound D-8 was used, Reference Comparative Example 2 corresponds to the case where ion pair compound D-9 was used, and Reference Comparative Example 3 corresponds to the case where ion pair compound D-10 was used. The evaluation results are shown in Table 1. When ion pair compound D-8 was used, thermal decomposition occurred during molding, and a molded product could not be obtained.

[0170] [Table 1]

[0171] [Examples 1 to 5, Comparative Example 1] <Production of Resin Composition> Polycarbonate resin PC-1, impact modifier composite acrylic resin B+C, and ion pair compound D-1 were mixed to a weight ratio of 70:30:1 to 70:30:11, and melt kneading and injection molding were performed in the same manner as in Reference Example 1 to mold a three-stage plate for evaluation (1 mmt, 2 mmt, 3 mmt). Using the molded three-stage plate, evaluations of antistatic properties, surface hardness, and impact resistance were performed based on the above evaluation method. In addition, during injection molding, a molded product (retention molded product) was also produced by retaining the resin in the cylinder for 10 minutes and then injecting it, and the thermal stability was evaluated by measuring the viscosity average molecular weight of the melt kneaded pellets and the retention molded product. Note that the polymerization ratio of the ion pair compound D-1 was 1 in Example 1 and 2 in Example 2. corresponds to a polymerization ratio of 2, Example 3 corresponds to a polymerization ratio of 3, Example 4 corresponds to a polymerization ratio of 5, Example 5 corresponds to a polymerization ratio of 8, and Comparative Example 1 corresponds to a polymerization ratio of 11. The evaluation results are shown in Tables 2 and 3.

[0172] [Example 6] <Production of Resin Composition> The polycarbonate resin PC-1, the impact modifier composite acrylic resin B+C, and the ion pair compound D-2 were mixed in a weight ratio of 70:30:2, and the same operations and evaluations were carried out as in Example 1. The evaluation results are shown in Table 2.

[0173] [Examples 7 to 8] <Production of Resin Composition> The same operations as in Example 1 were carried out, and the same evaluations were carried out, except that polycarbonate resin PC-1, impact modifier composite acrylic resin B+C, and ion pair compound D-3 were mixed in a weight ratio of 70:30:2 to 70:30:5. As for the polymerization ratio of ion pair compound D-3, Example 7 corresponds to a polymerization ratio of 2, and Example 8 corresponds to a polymerization ratio of 5. The evaluation results are shown in Table 2.

[0174] [Example 9] <Production of Resin Composition> The polycarbonate resin PC-1, the impact modifier composite acrylic resin B+C, and the ion pair compound D-4 were mixed in a weight ratio of 70:30:2, and the same operations and evaluations were carried out as in Example 1. The evaluation results are shown in Table 2.

[0175] [Examples 10 to 11] <Production of Resin Composition> Except for using polycarbonate resin PC-1, impact modifier composite acrylic resin B+C, and ion pair compound D-5 and mixing them so that the weight ratio was 70:30:2 to 70:30:5, the same operation as in Example 1 was performed and the same evaluation was performed. As for the polymerization ratio of ion pair compound D-5, Example 10 corresponds to a polymerization ratio of 2, and Example 11 corresponds to a polymerization ratio of 5. The evaluation results are shown in Table 2.

[0176] [Examples 12 to 13] <Production of Resin Composition> The same operations as in Example 1 were carried out, and the same evaluations were carried out, except that polycarbonate resin PC-1, impact modifier composite acrylic resin B+C, and ion pair compound D-6 were mixed in a weight ratio of 70:30:2 to 70:30:5. As for the polymerization ratio of ion pair compound D-6, Example 12 corresponds to a polymerization ratio of 2, and Example 13 corresponds to a polymerization ratio of 5. The evaluation results are shown in Table 2.

[0177] [Example 14] <Production of Resin Composition> The polycarbonate resin PC-1, the impact modifier composite acrylic resin B+C, and the ion pair compound D-7 were mixed in a weight ratio of 70:30:2, and the same operations and evaluations were carried out as in Example 1. The evaluation results are shown in Table 2.

[0178] [Comparative Example 2] <Production of Resin Composition> The same procedure as in Example 1 was attempted, except that polycarbonate resin PC-1, impact modifier composite acrylic resin B+C, and ion pair compound D-8 were mixed in a weight ratio of 70:30:2. However, the resin deteriorated significantly due to heat during processing, and samples could not be obtained. I didn't come.

[0179] [Comparative Example 3] <Production of Resin Composition> The polycarbonate resin PC-1, the impact modifier composite acrylic resin B+C, and the ion pair compound D-9 were mixed in a weight ratio of 70:30:2, and the same operations and evaluations were carried out as in Example 1. The evaluation results are shown in Table 3.

[0180] [Comparative Example 4] <Production of Resin Composition> The same operations and evaluations were carried out as in Example 1, except that polycarbonate resin PC-1, impact modifier composite acrylic resin B+C, and ion pair compound D-10 were mixed in a weight ratio of 70:30:2. The evaluation results are shown in Table 3.

[0181] [Comparative Example 5] <Production of Resin Composition> The same operations and evaluations were carried out as in Example 1, except that polycarbonate resin PC-1, impact modifier composite acrylic resin B+C, and antistatic agent E were mixed in a weight ratio of 70:30:2. The evaluation results are shown in Table 3.

[0182] [Comparative Examples 6 to 7] <Production of Resin Composition> Except for using polycarbonate resin PC-1, impact modifier composite acrylic resin B+C, and antistatic agent F and mixing them in a weight ratio of 70:30:4 to 70:30:10, the same operations as in Example 1 were performed and the same evaluations were carried out. As for the polymerization ratio of antistatic agent F, Comparative Example 6 corresponds to a polymerization ratio of 4, and Comparative Example 7 corresponds to a polymerization ratio of 10. The evaluation results are shown in Table 3.

[0183] [Examples 15 to 16] <Production of Resin Composition> The same operations as in Example 1 were carried out, and the same evaluations were carried out, except that polycarbonate resin PC-1, acrylic resin B-1, impact modifier C-1, and ion pair compound D-1 were mixed in a weight ratio of 70:15:15:2 to 70:15:15:5. As for the polymerization ratio of ion pair compound D-6, Example 15 corresponds to a polymerization ratio of 2, and Example 16 corresponds to a polymerization ratio of 5. The evaluation results are shown in Table 4.

[0184] [Example 17] <Production of Resin Composition> The same operations and evaluations were carried out as in Example 1, except that polycarbonate resin PC-1, acrylic resin B-1, impact modifier C-1, and ion pair compound D-3 were used and mixed in a weight ratio of 70:15:15:2. The evaluation results are shown in Table 4.

[0185] [Example 18] <Production of Resin Composition> The same operations and evaluations were carried out as in Example 1, except that polycarbonate resin PC-1, acrylic resin B-1, impact modifier C-1, and ion pair compound D-6 were used and mixed in a weight ratio of 70:15:15:2. The evaluation results are shown in Table 4.

[0186] [Example 19] <Production of Resin Composition> The same operations and evaluations were carried out as in Example 1, except that polycarbonate resin PC-1, acrylic resin B-1, impact modifier C-2, and ion pair compound D-1 were used and mixed in a weight ratio of 70:15:15:2. The evaluation results are shown in Table 4.

[0187] [Example 20] <Production of Resin Composition> The same operations and evaluations were carried out as in Example 1, except that polycarbonate resin PC-1, acrylic resin B-1, impact modifier C-3, and ion pair compound D-1 were used and mixed in a weight ratio of 70:15:15:2. The evaluation results are shown in Table 4.

[0188] [Example 21] <Production of polycarbonate resin> Using 294 parts of ISS, 400 parts of SPG, 22 parts of ND, and 750 parts of DPC as raw materials, the same operation as in Reference Example 1 was carried out to obtain pellets (PC-2). <Production of Resin Composition> The same operations and evaluations were carried out as in Example 1, except that polycarbonate resin PC-2, acrylic resin B-1, impact modifier C-1, and ion pair compound D-1 were used and mixed in a weight ratio of 70:10:20:2. The evaluation results are shown in Table 4. Polycarbonate resin PC-2 and ion pair compound D-1 were mixed in a ratio of 100:2, and the same procedure as in Reference Example 1 was carried out. The hydrophilicity of the molded article surface was evaluated by a water drop contact angle drop test, and the water drop contact angle R1 was 70°. D was 76°.

[0189] [Example 22] <Production of Resin Composition> The same operations and evaluations were carried out as in Example 1, except that polycarbonate resin PC-1, acrylic resin B-1, impact modifier C-1, and ion pair compound D-1 were used and mixed in a weight ratio of 40:30:30:2. The evaluation results are shown in Table 4.

[0190] [Example 23] <Production of Resin Composition> The same operations and evaluations were carried out as in Example 1, except that polycarbonate resin PC-1, acrylic resin B-1, impact modifier C-1, and ion pair compound D-1 were used and mixed in a weight ratio of 80:10:10:2. The evaluation results are shown in Table 4.

[0191] [Comparative Example 8] <Production of Resin Composition> The same operations and evaluations were carried out as in Example 1, except that polycarbonate resin PC-1, acrylic resin B-1, impact modifier C-1, and ion pair compound D-10 were mixed in a weight ratio of 70:15:15:2. The evaluation results are shown in Table 5.

[0192] [Comparative Example 9] <Production of polycarbonate resin> 450 parts of isosorbide (hereinafter abbreviated as ISS), 67 parts of 1,9-nonanediol (hereinafter abbreviated as ND), 750 parts of diphenyl carbonate (hereinafter abbreviated as DPC), and 0.0033 parts of barium stearate as a catalyst were heated to 150°C under a nitrogen atmosphere and melted. Thereafter, the mixture was sent to a reaction vessel, and the heat medium temperature of the condenser was adjusted to 40°C, the internal temperature of the resin was adjusted to 170°C, and the degree of vacuum was adjusted to 13.4 kPa over 30 minutes. Thereafter, the degree of vacuum was adjusted to 3.4 kPa over 20 minutes, and the temperature was maintained for 10 minutes. The degree of vacuum was further adjusted to 0.9 kPa over 30 minutes, the internal temperature of the resin was adjusted to 220°C, and the temperature was maintained for 10 minutes, after which the degree of vacuum was adjusted to 0.2 kPa. The viscosity was set to 100 Pa, the resin temperature was increased from 220°C to 240°C over 30 minutes, and after reaching a specified viscosity, the resin was discharged from the bottom of the reaction tank under nitrogen pressure, and while cooling in a water tank, it was cut with a pelletizer to obtain pellets (PC-3). Using the obtained pellets, injection molding was performed in the same manner as in Example 1, and the same evaluation was performed. The evaluation results are shown in Table 5.

[0193] [Comparative Example 10] <Production of Resin Composition> Except for using polycarbonate resin PC-3 and ion pair compound D-1 and mixing them in a weight ratio of 100:2, the same operations as in Example 1 were carried out and the same evaluations were carried out. The evaluation results are shown in Table 5.

[0194] [Comparative Example 11] The polycarbonate resin PC-3, the impact modifier C-1, and the ion pair compound D-1 were mixed in a weight ratio of 70:30:2, and the same operations and evaluations were carried out as in Example 1. The evaluation results are shown in Table 5.

[0195] [Comparative Example 12] The polycarbonate resin PC-3, the impact modifier composite acrylic resin B+C, and the ion pair compound D-1 were mixed in a weight ratio of 70:30:2, and the same operations and evaluations were carried out as in Example 1. The evaluation results are shown in Table 5.

[0196] [Comparative Example 13] The same operations and evaluations were carried out as in Example 1, except that polycarbonate resin PC-3, acrylic resin B-1, impact modifier C-1, and ion pair compound D-1 were used and mixed in a weight ratio of 70:15:15:2. The evaluation results are shown in Table 5.

[0197] [Comparative Example 14] The same operations and evaluations were carried out as in Example 1, except that polycarbonate resin PC-1, acrylic resin B-1, and ion-pair compound D-1 were used and mixed in a weight ratio of 70:30:2. The evaluation results are shown in Table 5.

[0198] [Comparative Example 15] <Production of Resin Composition> The polycarbonate resin PC-1 and the ion pair compound D-1 were used and mixed in a weight ratio of 100:2, and the same operations and evaluations were carried out as in Example 1. The evaluation results are shown in Table 5.

[0199] [Comparative Example 16] <Production of Resin Composition> The polycarbonate resin PC-1, the impact modifier C-1, and the ion pair compound D-1 were mixed in a weight ratio of 70:30:2, and the same operations and evaluations were carried out as in Example 1. The evaluation results are shown in Table 5.

[0200] [Table 2]

[0201] [Table 3]

[0202] [Table 4]

[0203] [Table 5] [Industrial Applicability]

[0204] The resin composition of the present invention is useful as a material for optical lenses, optical disks, optical films, plastic cell substrates, optical cards, liquid crystal panels, headlamp lenses, light guide plates, diffusion plates, protective films, OPC binders, front panels, housings, trays, aquariums, lighting covers, signs, plastic windows, and the like.

Claims

1. The resin composition contains 5 to 60 parts by weight of an impact modifier (C) and 0.1 to 10 parts by weight of an ion pair compound (D) relative to a total of 100 parts by weight of a polycarbonate resin (A) containing 5 to 85 mol% of carbonate structural units (a) represented by the following formula (1) out of 100 mol% of all carbonate structural units, and an acrylic resin (B), the weight ratio of the polycarbonate resin (A) to the acrylic resin (B) being 30:70 to 99:1, the ion pair compound has a melting point of 100°C or less, a 10% weight loss temperature measured by TG-TDA of 250°C or more, and satisfies the following formula [I], and the cation of the ion pair compound contains an organic ammonium ion or organic phosphonium ion represented by the following formula (3), or the anion of the ion pair compound contains a sulfonylimide ion represented by the following formula (4) or a fluorosulfonate ion represented by the following formula (5). R I >R D -30[I] (In the formula, R I is the contact angle (°) of a water droplet of a resin composition having an ion pair compound content of 2 parts by weight per 100 parts by weight of polycarbonate resin, and R D is the contact angle of a water droplet on polycarbonate resin (°). 【Chemistry 1】 (In the formula, W represents an alkylene group having 1 to 20 carbon atoms or a cycloalkylene group having 6 to 20 carbon atoms, R represents a branched or linear alkyl group having 1 to 20 carbon atoms or a cycloalkyl group having 6 to 20 carbon atoms which may have a substituent, and m represents an integer of 0 to 10.) [(R 1 ) 3 R 2 M] + (3) [In the formula, R 1 and R 2 represent a hydrocarbon group, and M represents a N atom or a P atom.] (R 3 SO 2 ) (R 4 SO 2 )N - (4) [In the formula, R 3 and R 4 each represent a perfluoroalkyl group.] R 5 SO 3 - (5) [In the formula, R 5 represents a perfluoroalkyl group.]

2. 2. The resin composition according to claim 1, wherein the polycarbonate resin (A) comprises a carbonate structural unit (a) represented by the formula (1) and another carbonate structural unit (b), and the carbonate structural unit (b) is a carbonate structural unit (b) derived from at least one compound selected from the group consisting of an aliphatic diol compound, an alicyclic diol compound, and an aromatic dihydroxy compound.

3. 3. The resin composition according to claim 1, wherein the acrylic resin (B) contains 40 to 100 mol % of a structural unit derived from methyl methacrylate.

4. The resin composition according to any one of claims 1 to 3, characterized in that the ion pair compound has a 10% weight loss temperature measured by TG-TDA of 270°C or higher and satisfies the following formula [II]: ( I  D _____] (In the formula, R I is the contact angle (°) of a water droplet of a resin composition having an ion pair compound content of 2 parts by weight per 100 parts by weight of polycarbonate resin, and R D is the contact angle of a water droplet on polycarbonate resin (°).

5. The cation of the ion pair compound contains an organic phosphonium ion represented by the following formula (6), or the anion of the ion pair compound contains a sulfonylimide ion represented by the following formula (7) or a fluorosulfonate ion represented by the following formula (8). The resin composition according to any one of claims 1 to 4. [(R 1 ) 3 R 2 P] + (6) [In the formula, R 1 is an alkyl group having one or more carbon atoms; R 2 represents an alkyl group having 4 or more carbon atoms. (R 3 SO 2 )(R 4 SO 2 )N - (7) [In the formula, R 3 , R 4 each represents a perfluoroalkyl group having 1 to 4 carbon atoms. R 5 SO 3 - (8) [In the formula, R 5 represents a perfluoroalkyl group having 1 to 4 carbon atoms.

6. The cation of the ion pair compound contains an organic phosphonium ion represented by the following formula (9), or the anion of the ion pair compound contains a sulfonylimide ion represented by the following formula (10) or a fluorosulfonate ion represented by the following formula (11). The resin composition according to any one of claims 1 to 5. [(R 1 ) 3 R 2 P] + (9) [In the formula, R 1 is an alkyl group having 4 or more carbon atoms, R 2 represents an alkyl group having 12 or more carbon atoms. (R 3 SO 2 )(R 4 SO 2 )N - (10) [In the formula, R 3 , R 4 each represents a trifluoromethyl group. R 5 SO 3 - (11) [In the formula, R 5 represents a perfluorobutyl group.

7. Notched Charpy impact strength measured according to ISO 179 is 10 kJ / m 2 The resin composition according to any one of claims 1 to 6.

8. The resin composition according to any one of claims 1 to 7, having a pencil hardness of H or more as measured in accordance with JIS K5400.

9. The surface resistivity of the molded product is 1 x 10 15 The resin composition according to any one of claims 1 to 8, wherein the elastic modulus is 0.05 to 0.5 (Ω / □) or less.

10. A molded article obtained by injection molding the resin composition according to any one of claims 1 to 9.

11. A film or sheet formed from the resin composition according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Reflector type photoelectric switch

    JP1987015717A

  • Antistatic resin composition

    JP2002129026A

  • Polycarbonate resin composition and compact thereof

    JP2014129488A

  • Resin composition

    JP2015232091A

  • Aromatic polycarbonate resin composition and compact thereof

    JP2018165315A